Ensuring curriculum relevance in vocational education and training: Epistemological perspectives in a curriculum research project - Hilde Hiim (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
This article addresses challenges regarding relevance in vocational education and training (VET) curricula. Recent research on Norwegian VET shows that the educational content is not sufficiently related to the students' needs for qualification in the actual vocations. I will present a new curriculum research project aimed at investigating and improving the vocational relevance in Norwegian VET. An important part of the project is to investigate epistemological perspectives on how vocational knowledge is constituted and developed, and consequences for the curriculum. The article presents results from these epistemological investigations. I will argue that the relevance problem relates to a one-sided rationalist epistemology in which a main idea is that vocational knowledge consists of theoretical principles and procedures to be applied in practical situations. This idea influences educational traditions and structures, and leads to a separation between theoretical and practical subjects and learning arenas. From a pragmatic epistemological perspective, it can be argued that vocational knowledge is contextual and holistic, and consists of complex wholes of physicality, motor skills, intellectual understandings, values, and verbalized concepts. To ensure curriculum relevance, a curriculum is needed in which authentic practical work is the base, and subjects are integrated with students' practical work experience.
Keywords: 330; VET; Vocational Education and Training; VET in Schools; Curriculum Development; Experiential Learning; Vocational Preparation